A plasmonic ellipse resonator possessing hybrid modes for ultracompact chipscale application. (21st October 2019) - Zhang, Zhaojian; Yang, Junbo; Xu, Heng; Xu, Siyu; Han, Yunxin; He, Xin; Zhang, Jingjing; Huang, Jie; Chen, Dingbo; Xie, Wanlin
Abstract: We propose a plasmonic ellipse resonator possessing hybrid modes based on a metal–insulator–metal waveguide system. Specially, this nanocavity has hybrid characteristic of rectangle and disk resonator, therefore supporting both Fabry–Perot modes (FPMs) and whispering-gallery modes (WGMs). Besides, by changing the length of major and minor radius of the ellipse, the resonant wavelengths of FPMs and WGMs can be independently tuned and close to each other, thus constructing a plasmon-induced transparency—like spectrum profile. Benefitting from this, a dual-band slow light is achieved with one single resonator. Furthermore, this component can also act as a multi-band color filter and refractive index sensor. We believe such a multi-mode resonator with an ultra-small footprint will play an important role in more compact on-chip optical circuits in the future.